Quality Test of Hybrid Corn Seeds Based on the Position of the Seeds on the Cob with a Comparison of the Parental Ratios that Have Been Applied with Trichoderma sp. - Muhanniah (Postgraduate, University of Mataram, 2024)
Seeds are a means of production whose quality must be guaranteed and maintained. The seed production, quality testing is an important part. This research aims to determine the effect of seed position on the cob, ratio comparison, and application of Trichoderma sp. on the quality of hybrid corn seeds. This research was carried out in BALITSEREAL, Maros Regency from September to October 2018. This research used a 3-factor factorial design method with a Completely Randomized Basic Design with each treatment combination consisting of 3 replications. The results showed that the position of the base seed had an effect on PK 11.63cm, JAS 4.51. The position of the middle seed has an effect on BKKN 12.31g, DHL 8.19 (cm-2). A ratio of 1:2 has an effect on a JAS of 4.47. A ratio of 1:3 has an effect on a PAP of 16.84cm. Trichoderma sp. 108 has an effect on DHL 9.56 (cm-2). The interaction of the position of the middle seed with a ratio of 1:2 has an effect on BKKN 12.85g. The interaction of base seed position with a ratio of 1:2 has an effect on JAS 4.77. The interaction of base seed position with a ratio of 1:3 had an effect on DB of 99.33%. The interaction between middle seed position and Trichoderma sp. 104 has an effect on BKKN 12.89g. The interaction between seed base position and Trichoderma sp. 104 had an effect on JAS 4.83, PK 12.29cm. The interaction ratio of 1:3 with Trichoderma sp. 10 4 has an effect on BKKN 12.39g. The interaction ratio of 1:3 with Trichoderma sp.10 8 has an effect on PK 11.82cm. The interaction ratio of 1:2 with Trichoderma sp.10 8 has an effect on JAS I4.86, DHL 8.97 (cm-2). Interaction of seed base position, ratio 1:2 and Trichoderma sp. 108 has an effect on JAS 5.60. The interaction of base seed position, ratio 1:3 and Trichoderma sp.10 8 has an effect on PK 13.15cm. Interaction of middle seed position, ratio 1:3 and Trichoderma sp. 10 4 has an effect on BKKN 13.80g on the quality of hybrid corn seeds.